Membrane nanodomains modulate formin condensation for actin remodeling in Arabidopsis innate immune responses. Issue 1 (2nd November 2021) - Ma, Zhiming; Sun, Yanbiao; Zhu, Xinlu; Yang, Liang; Chen, Xu; Miao, Yansong
Abstract: The assembly of macromolecules on the plasma membrane concentrates cell surface biomolecules into nanometer- to micrometer-scale clusters (nano- or microdomains) that help the cell initiate or respond to signals. In plant–microbe interactions, the actin cytoskeleton undergoes rapid remodeling during pathogen-associated molecular pattern-triggered immunity (PTI). The nanoclustering of formin-actin nucleator proteins at the cell surface has been identified as underlying actin nucleation during plant innate immune responses. Here, we show that the condensation of nanodomain constituents and the self-assembly of remorin proteins enables this mechanism of controlling formin condensation and activity during innate immunity in Arabidopsis thaliana . Through intrinsically disordered region-mediated remorin oligomerization and formin interaction, remorin gradually recruits and condenses formins upon PTI activation in lipid bilayers, consequently increasing actin nucleation in a time-dependent manner postinfection. Such nanodomain- and remorin-mediated regulation of plant surface biomolecules is expected to be a general feature of plant innate immune responses that creates spatially separated biochemical compartments and fine tunes membrane physicochemical properties for transduction of immune signals in the host. Abstract : Plant plasma membrane compartmentalization condenses actin nucleator-type-I formins to remodel actin cytoskeleton during immune signaling.